The reality of including the values of knowledge passion in the books of My Eternal Language in the intermediate stage in the Kingdom of Saudi Arabia - Al-Dosari, Mashael Saleh; Al-Ahmadi, Ebtehal Yehya (Journal of Curriculum and Teaching Methodology, 2023)
The aim of this research is to reveal the degree of cognitive passion values in Intermediate stage’s Arabic Language books in the Kingdom of Saudi Arabia. The two researchers used descriptive method represented by the content analysis approach. The research sample was formed of all the Arabic Language books of Intermediate stage, first and second term 1443 AH edition. For this purpose, the researchers prepared a content analysis tool that was built in view of the values of cognitive passion, it consisted of four main values. The results of the research reached to: Including the values of cognitive passion in the Arabic Language books of the intermediate stage is in a low-percentages. The results showed a significant difference in the distribution of cognitive passion values on the intermediate stage in general, some values have been emphasized while others have been marginalized.